Poly-DL-Lactic Acid (PDLLA) Nanosheet Thin Films for Biomedical, Bioengineering and Energy Saving Applications - Mohd Danial, Ibrahim; Sitti Aishah, Najamudin; Dayang Salyani, Abang Mahmod; Barroy, Pierre; Cantaluppi, Anna; Lejeune, Michaël; Zeinert, Andreas; Sunami, Yuta (2021)
PDLLA nanosheet thin films with different thickness of from 50nm to 150nm were investigated. Contact angle, profilometry and Fourier Transform InfraRed (FTIR) spectroscopy measurements were performed. It is shown that thinner PDLLA nanosheets could be more relevant for biomedical applications. Meanwhile, thicker nanosheets could be more suitable for bioengineering applications. Potential energy saving through bioinspired surfaces will also be presented through biomimicry patterning of the nanosheets surface.